Combination of torrefaction and catalytic fast pyrolysis for aromatic hydrocarbon production from herbaceous medicine waste. (1st May 2023) - Tang, Shouhang; Zhou, Sicheng; Li, Ge; Xin, Shanzhi; Huang, Fang; Liu, Xiaoye; Huang, Kai; Zeng, Lixi; Mi, Tie
Abstract: The combination of torrefaction pretreatment and catalytic pyrolysis of herbaceous medicine waste (HMW) was performed. The effects of torrefaction, pyrolysis temperature, SiO2 /Al2 O3 atomic ratio (SAR) and catalyst-to-feedstock (C/F) ratio on the distribution of aromatic hydrocarbons (AHs) was investigated. The formation of coke and its effects on the catalytic performance of the catalyst were evaluated. The results demonstrated that zeolite can effectively convert the torrefied HMW into AHs. The liquid products were dominated by monocyclic aromatic hydrocarbons (MAHs), in which toluene and xylene were formed preferentially over other aromatics. The total content of benzene, toluene, ethylbenzene, p-xylene, and naphthalene (BTEXN) reached 49.23–76.31%. Temperature, SAR and C/F ratio exhibit a greater influence on AHs formation than the torrefaction agents. A higher pyrolysis temperature and C/F ratio can inhibit coke formation, while higher SAR is beneficial to coke formation. The catalyst with a lower SAR yield more AHs and less coke. Coke was initially formed on the surface of the catalyst at low temperature, but it was more likely to form in the pores of the catalyst at high temperatures. The results show that the combination of torrefaction and catalytic pyrolysis is a potential approach for converting HMW into valuable bio-oils. Graphical abstract: Image 1 Highlights: Torrefaction and catalytic pyrolysis of herbaceous medicine waste was performed. Zeolite can effectively convert the torrefied HMW into aromatic hydrocarbons. Lower pyrolysis temperature and SAR of catalyst was beneficial to BTEXN formation. Coke deposition during pyrolysis decreases the activity of zeolite catalyst. Oxygenated compounds were the coke precursors during catalytic pyrolysis.